Contrived Competition and Manufactured Uncertainty: Understanding Managerial Job Insecurity Narratives in Large Corporations. (June 2018) - Hassard, John; Morris, Jonathan
The article addresses the debate over insecurity and precarity in managerial work. It notes while some commentators suggest advanced economies are characterized by managerial job insecurity, others argue the same economies possess stable managerial tenure rates. To make sense of this conundrum, qualitative data from semi-structured interviews with managers working in large corporations in liberal-market (USA, UK) and coordinated-market (Japan) societies are analysed. The aim is to assess whether sensitivity to managerial job insecurity is widespread and if so reflects wider corporate strategies of 'contrived competition' and 'manufactured uncertainty'. It is argued such notions can influence managers' understanding of their work situation through (re)producing narratives of employment precarity. Contrary to the message from many database and questionnaire studies, evidence from this international and longitudinal study suggests awareness of job insecurity is indeed widespread and does affect managers' views of their employment situation and prospects.